Students' performance evaluation in online education system Vs traditional education system - Jayasinghe, Udeni; Dharmaratne, Anuja; Atukorale, Ajantha (2015 12th International Conference on Remote Engineering and Virtual Instrumentation (REV), 2015)
Nowadays most of the education institutes practice online teaching mechanism rather than using the traditional teacher centered teaching mechanism to enhance the learning ability of the students by making a student centered learning mechanism. The teachers have to evaluate the students' performance no matter what their learning mechanism is and there are ways of doing that i.e. formal evaluation and informal evaluation. That means by giving exam papers and giving feedbacks based on the students' behavior. When it comes to online education mechanism, there are no teachers to monitor the behavior of the students. Now researchers have come up with various ideas to measure the emotional level and behavior of the students and to respond according to each and every student through the online education systems. The aim of this article is to review some literature and to do a comparison among the various proposed ideas of researchers whose aim was to evaluate the performance of the students who are engaged in online education systems.